PENERAPAN BONEKA JARI SEBAGAI MEDIA BIMBINGAN UNTUK MENINGKATKAN KECERDASAN SPIRITUAL ANAK DI LEARNING QURAN FOR ALL (LQA) SAHABAT-QU YOGYAKARTA - Siti Triyuwanti; Lailatul Widha (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2018)
Children are individuals who have a very rapid development process and are very fundamental to the next life. The age of children who are in the development period has a great opportunity directed towards becoming a person who tends to be positive or negative. Thus, the child needs to be guided to motivate the tendency to virtue which is essentially an attempt to actualize the spiritual potential of the child. In accordance with the title of this study, the application of finger puppets as a medium of guidance to improve children's spiritual intelligence in LQA (Learning Quran For All) Yogyakarta Friends. This research is a study that provides guidance to children aged 5-7 years who are in Tahsin 1 class with a total of 7 people in LQA Sahabat-Qu Yogyakarta. This research is a field research with a qualitative approach and uses participant observation methods and documentation in collection. The purpose of this study is to obtain effective and characterized guidance methods that can improve the quality of children's self, especially in guidance in improving children's spiritual intelligence.